2013
DOI: 10.1093/mnras/stt1126
|View full text |Cite
|
Sign up to set email alerts
|

The near-infrared Ca ii triplet as a metallicity indicator – II. Extension to extremely metal-poor metallicity regimes★

Abstract: We extend our previous calibration of the infrared Ca ii triplet as metallicity indicator to the metal-poor regime by including observations of 55 field stars with [Fe/H] down to -4.0 dex. While we previously solved the saturation at high-metallicity using a combination of a Lorentzian plus a Gaussian to reproduce the line profiles, in this paper we address the non-linearity at low-metallicity following the suggestion of Starkenburg et al. (2010) of adding two non-linear terms to the relation among the [Fe/H],… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
183
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(192 citation statements)
references
References 85 publications
5
183
2
2
Order By: Relevance
“…Many authors have confirmed the accuracy and repeatability of CaT abundance measurements in combination with broad-band optical photometry and shown its very high sensitivity to metallicity and insensitivity to age (e.g., Cole et al 2004). Additionally, as reported by Carrera et al (2013), the strength of the CaT lines depends mainly on iron abundances, and not on the Ca abundance, as has been pointed out also by several other investigations (e.g. Idiart et al 1997;Battaglia et al 2008).…”
Section: Introductionmentioning
confidence: 55%
“…Many authors have confirmed the accuracy and repeatability of CaT abundance measurements in combination with broad-band optical photometry and shown its very high sensitivity to metallicity and insensitivity to age (e.g., Cole et al 2004). Additionally, as reported by Carrera et al (2013), the strength of the CaT lines depends mainly on iron abundances, and not on the Ca abundance, as has been pointed out also by several other investigations (e.g. Idiart et al 1997;Battaglia et al 2008).…”
Section: Introductionmentioning
confidence: 55%
“…We prefer to use that calibration because it is based on moderate-resolution near-IR spectroscopy in the K band, which is similar to our spectral database. Moreover, the later work of Carrera et al (2013) shows that the metallicity vs. spectral index relation of globular and open clusters can be successfully combined and thus the range A24, page 4 of 25 Gray circles are all stars within the estimated cluster radius, dark circles are probable cluster members that remained after statistical decontamination. Stars with spectra are denoted by red circles and are labeled.…”
Section: Cluster Search and Methods Of Analysismentioning
confidence: 99%
“…However, Starkenburg et al (2010) have demonstrated that this assumption is not valid, particularly for metal-poor regimes. For this reason, Carrera et al (2013) recomputed the Carrera et al (2007) relationships, introducing two additional terms to account for the non-linearity effects. In any case, these authors have demonstrated that both calibrations produce similar results, within ±0.2 dex, in the range of metallicities expected for open clusters.…”
Section: Membership Selection Radial Velocity and Metallicity Determmentioning
confidence: 99%